2017
DOI: 10.1088/2053-1583/aa6b72
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic effects in the optical properties of 2D materials:an equation of motion approach

Abstract: Abstract. We present a unified description of the excitonic properties of four monolayer transition-metal dichalcogenides (TMDC's) using an equation of motion method for deriving the Bethe-Salpeter equation in momentum space. Our method is able to cope with both continuous and tight-binding Hamiltonians, and is less computational demanding than the traditional first-principles approach. We show that the role of the exchange energy is essential to obtain a good description of the binding energy of the excitons.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 57 publications
8
68
0
Order By: Relevance
“…Comparing to the spectra of unperturbed TMDs in Ref. 9, we see that the qualitative features agree well.…”
Section: Excitonic Effectssupporting
confidence: 70%
“…Comparing to the spectra of unperturbed TMDs in Ref. 9, we see that the qualitative features agree well.…”
Section: Excitonic Effectssupporting
confidence: 70%
“…This provides the relation between the polarization operator and the field in the 2D material. The solution, which describes the optical response of the TMD, leads to the an Elliotttype formula appropriate for the 2D material 52 . This allows us to calculate the absorption, via the reflection operator's expectation value, taking into account the contributions of both γ r,0 (and its Purcell enhancement), γ nr , and γ d .…”
Section: Arxiv:190807598v6 [Physicsoptics] 9 Sep 2019mentioning
confidence: 99%
“…As the low‐energy physics of atomically thin TMDCs is well‐described by an effective Dirac‐like Hamiltonian with finite mass, the valley degree of freedom can be used to manipulate the spin polarization of electrons—due to the sizable spin‐orbit coupling exhibited by such materials—using circularly polarized light . Pioneering experiments have shown that it is possible to inject excitons with highly polarized spins that could be utilized for valleytronics .…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%